Resin composition, prepreg, resin sheet, laminate, metal foil-clad laminate, and printed circuit board

By using the combination of BaTi4O9 (A) and filler material (B) in the resin composition, combined with the choice of thermosetting resin (C), the contradiction between dielectric properties and thermal expansion properties of the insulating layer is solved, and a high dielectric constant is achieved , the balance of low dielectric loss tangent and low thermal expansion coefficient improves the insulation layer performance and appearance of printed circuit boards.

CN116457417BActive Publication Date: 2025-02-14MITSUBISHI GAS CHEM CO INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280007268.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-10
Filing Date
2022-01-26
Publication Date
2025-02-14
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

The prior art is difficult to simultaneously increase the relative dielectric constant of the insulating layer and reduce the dielectric loss tangent, resulting in an increase in the transmission loss of high-frequency electrical signals, while the uneven distribution of the filling material leads to deterioration of the appearance of the molded product.

Method used

By using the combination of BaTi4O9 (A) and different filler materials (B), by adjusting its volume ratio and average particle size, combined with the selection of thermosetting resin (C), we form a high dielectric constant, low dielectric loss tangent, and low thermal expansion coefficient. and a resin composition with good appearance.

Benefits of technology

A balance of obtaining high dielectric constant and low dielectric loss tangent in the insulating layer of the printed circuit board is achieved, reducing the thermal expansion coefficient and improving the appearance quality of the molded product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDF0000033793640000021
    Figure FDF0000033793640000021
  • Figure FDF0000033793640000022
    Figure FDF0000033793640000022
  • Figure FDF0000033793640000031
    Figure FDF0000033793640000031
Patent Text Reader

Abstract

The object is to provide a resin composition having a high dielectric constant and a low dielectric loss tangent, a low thermal expansion coefficient and a good appearance, which is suitable for the manufacture of an insulating layer of a printed circuit board, and a prepreg, a resin sheet, a laminate, a metal foil-clad laminate, and a printed circuit board obtained using the resin composition. The resin composition of the present invention comprises BaTi4O9 (A), a filler (B) different from the aforementioned BaTi4O9 (A), and a thermosetting resin (C), wherein the average particle size of the aforementioned BaTi4O9 (A) is 0.10 to 1.00 μm, and the aforementioned BaTi4O9 (A) and the aforementioned filler (B) are contained in a range of 15:85 to 80:20, expressed as a volume ratio (the aforementioned BaTi4O9 (A): the aforementioned filler (B)).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, a prepreg, a resin sheet, a laminate, a metal foil-clad laminate and a printed circuit board. Background Art

[0002] In recent years, the signal frequency band of information and communication equipment such as PHS and mobile phones, as well as the CPU clock time of computers have reached the GHz band, and high frequencies are being developed. The dielectric loss of an electrical signal is proportional to the product of the square root of the relative dielectric constant of the insulating layer forming the circuit, the dielectric loss tangent, and the frequency of the electrical signal. For this reason, the higher the frequency of the signal used, the greater the dielectric loss. Since the increase in dielectric loss will attenuate the electrical signal and damage the reliability of the signal, in order to suppress this situation, a material with a small dielectric constant and dielectric loss tangent must be selected in the insulating layer.

[0003] On the other hand, for the insulating layer of the high-frequency circuit, there are requirements such as the formation of a delay circuit, impedance matching of a circuit board in a low-impedance circuit, refinement of a wiring pattern, and composite circuitization with a built-in capacitor in the substrate itself, and sometimes a high dielectric constant of the insulating layer is required. Therefore, an electronic component using an insulating layer with a high dielectric constant and a low dielectric loss tangent is proposed (for example, Patent Document 1). The insulating layer with a high dielectric constant and a low dielectric loss tangent is formed by dispersing a filler material such as a ceramic powder and a metal powder subjected to an insulation treatment in a resin.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2000-91717 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, in order to increase the relative dielectric constant of the insulating layer, it is required to mix a filler having a high relative dielectric constant, but at the same time, the dielectric loss tangent also increases, so there is a problem that the transmission loss of the high-frequency signal increases.

[0009] In addition, fillers used to produce insulating layers with high dielectric constants and low dielectric loss tangents generally have high specific gravity, which may cause poor dispersion in the resin composition, uneven distribution of the fillers, and thus deteriorate the appearance of the molded product.

[0010] Furthermore, if the insulating layer has a high thermal expansion coefficient, warping and interface peeling may occur during the manufacture of the laminate. Therefore, in addition to having a high dielectric constant and a low dielectric loss tangent, it is also important for the filler used in the printed circuit board to have a low thermal expansion coefficient.

[0011] The present invention has been made to solve the above-mentioned problems, and its object is to provide: a resin composition having a high dielectric constant and a low dielectric loss tangent, a low thermal expansion coefficient and a good appearance, which is suitable for manufacturing an insulating layer of a printed wiring board, and a prepreg, a resin sheet, a laminate, a metal foil-clad laminate, and a printed wiring board obtained by using the resin composition.

[0012] That is, the present invention is as follows.

[0013] [1] A resin composition comprising:

[0014] BaTi 4 O 9 (A)

[0015] Different from the aforementioned BaTi 4 O 9 (A) filler material (B), and

[0016] Thermosetting resin (C),

[0017] The aforementioned BaTi 4 O 9 The average particle size of (A) is 0.10 to 1.00 μm,

[0018] By volume ratio (the aforementioned BaTi 4 O 9 (A): The aforementioned filler (B)) contains the aforementioned BaTi in a range of 15:85 to 80:20 4 O 9 (A) and the aforementioned filling material (B).

[0019] [2] The resin composition according to [1], wherein the filler (B) comprises one or more selected from the group consisting of silica, alumina, calcium titanate, strontium titanate, aluminum nitride, boron nitride, boehmite, aluminum hydroxide, silicone rubber powder and silicone composite powder.

[0020] [3] The resin composition according to [1] or [2], wherein the BaTi 4 O 9 The total content of (A) and the filler (B) is 100 to 300 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.

[0021] [4] The resin composition according to any one of [1] to [3], wherein the thermosetting resin (C) comprises one or more selected from the group consisting of cyanate compounds, maleimide compounds, epoxy compounds, phenol compounds, alkenyl-substituted nadic imide compounds, oxetane resins, benzoxazine compounds, and compounds having a polymerizable unsaturated group.

[0022] [5] The resin composition according to [4], wherein the cyanate ester compound comprises one or more selected from the group consisting of phenol novolac type cyanate ester compounds, naphthol aralkyl type cyanate ester compounds, naphthyl ether type cyanate ester compounds, xylene resin type cyanate ester compounds, bisphenol M type cyanate ester compounds, bisphenol A type cyanate ester compounds, diallyl bisphenol A type cyanate ester compounds, bisphenol E type cyanate ester compounds, bisphenol F type cyanate ester compounds, and biphenyl aralkyl type cyanate ester compounds, and prepolymers or polymers of these cyanate ester compounds.

[0023] [6] The resin composition according to [4] or [5], wherein the maleimide compound comprises one or more selected from the group consisting of bis(4-maleimidephenyl)methane, 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane, bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, a maleimide compound represented by the following formula (2), a maleimide compound represented by the following formula (3), and a maleimide compound represented by the following formula (4).

[0024]

[0025] In formula (2), R 1 Each independently represents a hydrogen atom or a methyl group, and n1 is an integer of 1-10.

[0026]

[0027] In formula (3), R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a phenyl group, and n2 is an average value, which represents 1 <n2≤5。

[0028]

[0029] In formula (4), Ra each independently represents a hydrogen atom, an alkyl group, an alkoxy group or an alkylthio group having 1 to 10 carbon atoms, an aryl group, an aryloxy group or an arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a nitro group, a hydroxyl group or a mercapto group. q represents an integer of 0 to 4. When q is an integer of 2 to 4, Ra may be the same or different in the same ring. Rb each independently represents a hydrogen atom, an alkyl group, an alkoxy group or an alkylthio group having 1 to 10 carbon atoms, an aryl group, an aryloxy group or an arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a hydroxyl group or a mercapto group. r represents an integer of 0 to 3. When r is 2 or 3, Rb may be the same or different in the same ring. n represents the average number of repeating units, and represents a value of 0.95 to 10.0.

[0030] [7] The resin composition according to any one of [4] to [6], wherein the epoxy compound comprises one or more selected from the group consisting of biphenyl aralkyl epoxy resins, naphthalene epoxy resins, naphthyl ether epoxy resins, and butadiene skeleton-containing epoxy resins.

[0031] [8] The resin composition according to any one of [1] to [7], which is used for a printed wiring board.

[0032] [9] A prepreg comprising:

[0033] substrate; and,

[0034] The resin composition according to any one of [1] to [8] impregnated or coated on the substrate.

[0035]

[10] A resin sheet comprising the resin composition according to any one of [1] to [8].

[0036]

[11] A laminate comprising at least one selected from the group consisting of the prepreg described in [9] and the resin sheet described in

[10] .

[0037]

[12] A metal foil-clad laminate comprising:

[0038]

[11] The laminated plate; and

[0039] A metal foil is disposed on one or both sides of the laminate.

[0040]

[13] A printed circuit board having:

[0041] Insulation layer; and,

[0042] A conductor layer disposed on one or both sides of the insulating layer,

[0043] The insulating layer includes a cured product of the resin composition according to any one of [1] to [8].

[0044] Effects of the Invention

[0045] According to the resin composition of the present invention, there can be provided: a resin composition having a high dielectric constant and a low dielectric loss tangent, as well as a low thermal expansion coefficient and a good appearance, which is suitable for manufacturing an insulating layer of a printed circuit board, and a prepreg, a resin sheet, a laminate, a metal foil-clad laminate, and a printed circuit board obtained using the resin composition. DETAILED DESCRIPTION

[0046] Hereinafter, a method for implementing the present invention (hereinafter referred to as "this embodiment") is described in detail. The following this embodiment is an example for illustrating the present invention, and is not intended to limit the present invention to the following content. The present invention can be implemented with appropriate deformation within the scope of its purpose.

[0047] It should be noted that, in the present embodiment, "resin solid content" or "resin solid content in the resin composition" refers to the resin composition except BaTi, unless otherwise specified. 4 O 9 (A), filler (B), additives, and resin components other than solvents. "100 parts by mass of resin solid content" refers to the resin composition except BaTi 4 O 9 The total amount of the resin components other than (A), the filler (B), the additives, and the solvent is 100 parts by mass.

[0048] [Resin composition]

[0049] The resin composition of this embodiment includes: BaTi 4 O 9 (A) Different from BaTi 4 O 9 (A) filler (B), and thermosetting resin (C), BaTi 4 O 9 The average particle size of (A) is 0.10 to 1.00 μm, and the volume ratio (the aforementioned BaTi 4 O 9 (A): The aforementioned filler (B) contains BaTi in a range of 15:85 to 80:20. 4 O 9 (A) and filling material (B).

[0050] <BaTi 4 O9(A)>

[0051] The resin composition of this embodiment contains BaTi 4 O 9 (A) BaTi 4O 9 (A) can be used alone or in combination of two or more kinds having different average particle sizes (D50).

[0052] In this embodiment, the resin composition comprises: BaTi having a specific average particle size 4 O 9 (A), the filler (B) described later, and the thermosetting resin (C) described later, containing BaTi in a specific volume ratio 4 O 9 When (A) and the filler (B) are combined, an insulating layer for a printed circuit board having a high dielectric constant and a low dielectric loss tangent, a low thermal expansion coefficient and a good appearance can be obtained. The reason for this is not clear, but the present inventors presume as follows.

[0053] That is, for BaTi with an average particle size (D50) of 0.10 to 1.00 μm 4 O 9 (A) can maintain high dispersibility even when the filler (B) is included in a resin composition such as a resin varnish. 4 O 9 (A) and filler (B) are used in a specific volume ratio, so that BaTi 4 O 9 (A) and filler (B) are less likely to be unevenly distributed and aggregated in the thermosetting resin (C). 4 O 9 (A) is suitably dispersed with filler (B), and is not easy to produce the sedimentation caused by uneven distribution and aggregation. In addition, owing to being well dispersed in the resin combination, therefore, the thermal expansion coefficient of the insulating layer can be suitably controlled, and the dielectric path in the insulating layer can be effectively formed. For this reason, it is inferred that: according to the resin combination of the present embodiment, there is a high dielectric constant and a low dielectric loss tangent and a thermal path can also be effectively formed, so it is possible to obtain an insulating layer with a low thermal expansion coefficient, further having a good appearance. However, the reason is not limited to this.

[0054] BaTi 4 O 9The average particle size (D50) of (A) is 0.10 to 1.00 μm, preferably 0.20 to 0.80 μm, and more preferably 0.25 to 0.50 μm. If the average particle size (D50) is within the above range, even if the filler (B) is contained in a resin composition such as a resin varnish, there is a tendency to maintain high dispersibility and effectively form a dielectric path in the insulating layer. It should be noted that in this specification, the average particle size (D50) refers to the value when the volume accumulation from the smallest particles reaches 50% of the total volume by measuring the particle size distribution of a specified amount of powder put into a dispersion medium using a laser diffraction scattering particle size distribution measuring device. The average particle size (D50) can be calculated by measuring the particle size distribution using a laser diffraction / scattering method, and the specific measurement method can be referred to the embodiment.

[0055] BaTi 4 O 9 The relative dielectric constant of (A) is preferably 20 or more, more preferably 25 or more. If the relative dielectric constant is 20 or more, there is a tendency to obtain an insulating layer having a high relative dielectric constant. 4 O 9 The relative dielectric constant of (A) is a value at 40 GHz according to the open resonator method. 4 O 9 The relative dielectric constant of (A) can be calculated using the Bruggeman formula (composite rule).

[0056] BaTi 4 O 9 The dielectric loss tangent of (A) is preferably 0.01 or less, and more preferably 0.008 or less. If the dielectric loss tangent is 0.01 or less, there is a tendency to obtain an insulating layer having a low dielectric loss tangent. It should be noted that in this embodiment, BaTi 4 O 9 The dielectric loss tangent of (A) is a value at 40 GHz according to the open resonator method. 4 O 9 The dielectric loss tangent of (A) can be calculated using the Bruggeman formula (composite rule).

[0057] The resin composition of this embodiment has a volume ratio (BaTi 4 O 9 (A): Filler (B)) contains BaTi in the range of 15:85 to 80:20 4 O 9 (A) and the filler (B) described later. If the volume ratio is within the above range, BaTi 4 O9 (A) and the filler (B) are well dispersed in a resin composition such as a resin varnish, and uneven distribution and aggregation are less likely to occur, so that a molded product with a good appearance can be obtained. In addition, since it is well dispersed in the resin composition, the thermal expansion coefficient of the insulating layer can be appropriately controlled, and the dielectric path in the insulating layer can be effectively formed. Therefore, there is a tendency to appropriately obtain an insulating layer with a low thermal expansion coefficient, a high dielectric constant and a low dielectric loss tangent. From the perspective of obtaining an insulating layer with a lower thermal expansion coefficient, a higher dielectric constant and a lower dielectric loss tangent, and obtaining a molded product with a better appearance, the volume ratio is preferably in the range of 20:80 to 75:25, more preferably in the range of 25:75 to 70:30, further preferably in the range of 25:75 to 65:35, and further more preferably in the range of 30:70 to 60:40. BaTi 4 O 9 In the volume ratio of (A) to the filler (B) described later, BaTi 4 O 9 When (A) is less than 20 and the filler (B) described later is more than 80, there is a concern that the relative dielectric constant is low, the dispersibility is deteriorated, and the appearance is poor. 4 O 9 When (A) exceeds 75 and the filler (B) described later is less than 25, there is a concern that the dielectric loss tangent and the thermal expansion coefficient may increase.

[0058] BaTi 4 O 9 The total content of (A) and the filler (B) described later is preferably 100 to 300 parts by mass, more preferably 120 to 280 parts by mass, and even more preferably 150 to 270 parts by mass, based on 100 parts by mass of the resin solid content in the resin composition. 4 O 9 When (A) and the filler (B) are further dispersed in the thermosetting resin (C), the thermal expansion coefficient of the insulating layer can be more appropriately controlled, and there is a tendency that the dielectric path in the insulating layer can be formed more efficiently.

[0059] For BaTi 4 O 9 The content of (A) is preferably 70 to 280 parts by mass, more preferably 80 to 270 parts by mass, relative to 100 parts by mass of the resin solid content in the resin composition, from the viewpoints of better dispersibility with the filler (B) described later in the resin composition, less prone to uneven distribution and aggregation, more suitable control of the low thermal expansion coefficient of the insulating layer, and more effective formation of the dielectric path in the insulating layer.

[0060] (BaTi 4 O 9 (A) and a method for producing a slurry)

[0061] BaTi of this embodiment 4 O 9 The method for producing (A) is not particularly limited, and a known method can be used. As such method, for example, the following method can be cited: titanium oxide (TiO 2 ) and barium carbonate (BaCO 3 ) are mixed in a predetermined molar ratio and then sintered in the atmosphere. The sintered product can be adjusted to a BaTi with a predetermined average particle size (D50) using a known pulverizer. 4 O 9 (A) As a pulverizer, for example, a ball mill, a sand mill, a continuous bead mill, etc. can be used.

[0062] In this embodiment, BaTi 4 O 9 (A) can be used in the form of a slurry. 4 O 9 The slurry (A) is not particularly limited and can be obtained by a known method. For example, the sintered product or commercially available BaTi is added to a known organic solvent such as methyl ethyl ketone. 4 O 9 (raw material), forming BaTi 4 O 9 After the solution (s), the BaTi in the solution (s) is crushed by a pulverizer. 4 O 9 The BaTiO2 is pulverized, uniformly mixed and dispersed, thereby preparing BaTiO2 with a specified average particle size (D50). 4 O 9 (A) slurry. In addition, the raw material BaTi 4 O 9 Pre-crushing can be carried out in a pulverizer as required.

[0063] As BaTi 4 O 9 Examples of the raw material of (A) include BT-149 (trade name, average particle size (D50): 2.1 μm, Nippon Chemical Industry Co., Ltd.).

[0064] BaTi 4 O 9 BaTi in solution(s) 4 O 9 The concentration of BaTi is not particularly limited, but is preferred from the perspective of excellent dispersibility and productivity. 4 O 9The solution (s) is 100% by mass, and is preferably 35 to 60% by mass in terms of solid content.

[0065] BaTi 4 O 9 The solution (s) preferably contains a wetting dispersant. As the wetting dispersant, reference can be made to the following description. 4 O 9 The solution (s) contains 0.1 to 5 parts by mass of a wetting and dispersing agent in an amount of 100 parts by mass.

[0066] The pulverizing method is not particularly limited, and for example, wet pulverization using a bead mill can be cited. As a pulverizer, a continuous bead mill can be cited. Among them, from the aspect of easily adjusting the average particle size (D50) to a specified range and obtaining uniform particles, a continuous bead mill is preferably used.

[0067] The beads used in the bead mill are not particularly limited, and examples thereof include zirconia beads, zirconia / silica ceramic beads, alumina beads, and silica ceramic beads. Among these, zirconia beads and zirconia / silica ceramic beads are preferred because of their high pulverization efficiency, ease of adjustment to a predetermined average particle size (D50), and resistance to breakage.

[0068] The particle size of the beads is not particularly limited, but is preferably 0.01 to 3 mm, more preferably 0.05 to 1 mm, and still more preferably 0.05 to 0.5 mm. If the particle size of the beads is less than 0.01 mm, the average particle size (D50) is difficult to control and the beads are easily broken, so it is difficult to obtain BaTi with a predetermined average particle size (D50). 4 O 9 In addition, if the particle size of the beads exceeds 3 mm, the grinding speed will decrease, and it will be difficult to obtain BaTi with an average particle size (D50) of 1.0 μm or less. 4 O 9 The amount of beads filled is preferably 40 to 70% by volume, more preferably 50 to 65% by volume, relative to the volume of the grinding chamber of the bead mill.

[0069] In addition, in this embodiment, before pulverizing, a disperser can be used to mix the organic solvent with BaTi. 4 O 9 Mix to make BaTi 4 O 9 Dispersed in an organic solvent to obtain BaTi 4 O 9 Solution(s).

[0070] For the BaTi in the obtained slurry 4 O 9The concentration of (A) is preferably 30 to 60% by mass in terms of solid content relative to 100% by mass of the slurry from the viewpoint of excellent dispersibility and productivity.

[0071] <Filling material (B)>

[0072] The resin composition of this embodiment includes a 4 O 9 (A) filler (B). As filler (B), as long as it is different from BaTi 4 O 9 There are no particular limitations on (A). The filler (B) may be used alone or in combination of two or more.

[0073] The average particle size (D50) of the filler (B) is preferably 0.10 to 10.00 μm, more preferably 0.30 to 5.00 μm. If the average particle size (D50) is within the above range, the filler (B) has a uniform particle size with respect to the BaTi in the resin composition. 4 O 9 (A) has a better dispersibility, is less likely to produce uneven distribution and aggregation, and has a tendency to further improve the appearance of the molded product, low dielectric loss tangent, and low thermal expansion coefficient. The average particle size (D50) of the filler (B) can be the same as that of the above-mentioned BaTi 4 O 9 The average particle size (D50) of (A) was calculated in the same manner.

[0074] Examples of the filler (B) include silicon dioxide, silicon compounds (such as white carbon), metal oxides (such as aluminum oxide, titanium dioxide, strontium titanate (SrTiO 3 ), TiO 2 MgSiO 4 MgTiO 3 、ZnTiO 3 、ZnTiO 4 、CaTiO 3 、SrTiO 3 、SrZrO 3 ,BaTi 2 O 5 , Ba 2 Ti 9 O 20 、Ba(Ti,Sn) 9 O 20 、ZrTiO 4 、(Zr,Sn)TiO 4 、BaNd 2 Ti 5 O 14、BaSmTiO 14 、Bi 2 O 3 -BaO-Nd 2 O 3 -TiO 2 ,La 2 Ti 2 O 7 、BaTiO 3 、Ba(Ti,Zr)O 3 、(Ba,Sr)TiO 3 , zinc oxide, magnesium oxide, and zirconium oxide, etc.), metal nitrides (such as boron nitride, silicon nitride, and aluminum nitride, etc.), metal sulfur oxides (such as barium sulfate, etc.), metal hydroxides (such as aluminum hydroxide, aluminum hydroxide heat-treated products (such as aluminum hydroxide heated to reduce a portion of the crystal water), boehmite, and magnesium hydroxide, etc.), zinc compounds (such as zinc borate and zinc stannate, etc.), clay, kaolin, talc, sintered clay, sintered kaolin, sintered talc, mica, E-glass, A-glass, NE-glass, C-glass, L-glass, D-glass, S-glass, M-glass, etc. - Inorganic fillers such as glass G20, glass staple fibers (including glass powders such as E glass, T glass, D glass, S glass, and Q glass), hollow glass, spherical glass, and metal particles with insulation treatment for gold, silver, palladium, copper, nickel, iron, cobalt, zinc, Mn-Mg-Zn series, Ni-Zn series, Mn-Zn series, carbonyl iron, Fe-Si series, Fe-Al-Si series, and Fe-Ni series; styrene-type, butadiene-type, and acrylic-type rubber powders; core-shell-type rubber powders; silicone resin powders; silicone rubber powders; silicone composite powders, and other organic fillers.

[0075] Among these, for filler (B), from BaTi 4 O 9 (A) From the viewpoint of better dispersibility, less prone to uneven distribution and aggregation, and further improved low thermal expansion, it is preferred to contain one or more selected from the group consisting of silica, alumina, calcium titanate, strontium titanate, aluminum nitride, boron nitride, boehmite, aluminum hydroxide, silicone rubber powder, and silicone composite powder, and more preferably contains silica.

[0076] As silicon dioxide, for example, natural silicon dioxide, fused silica, synthetic silica, Aerosil and hollow silica etc. can be enumerated. These silicon dioxides can be used alone or in combination of two or more. Among these, fused silica and hollow silica are preferred from the aspects of having low thermal expansion coefficient, further excellent dispersibility in resin composition, becoming further difficult to produce uneven distribution, aggregation.

[0077] As silica, commercially available products may be used, and examples thereof include SC2050-MB, SC5050-MOB, SC2500-SQ, SC4500-SQ, and SC5050-MOB (these are trade names, manufactured by Admatechs Corporation); and SFP-130MC (trade name, manufactured by Denka Corporation).

[0078] In this embodiment, BaTi 4 O 9 (A) Other than BaTi 4 O 9 , that is, different from BaTi 4 O 9 (A) Average particle size (D50) of BaTi 4 O 9 It can be contained in the resin composition as a filler (B), but the BaTi in the resin composition is obtained. 4 O 9 From the viewpoint of excellent dispersibility of (A) and filler (B), it is preferred that BaTi is not contained. 4 O 9 (A) Other than BaTi 4 O 9 .

[0079] Regarding the content of the filler (B), the content of the filler (B) in the resin composition is determined by the following steps: 4 O 9 From the viewpoint of further improving the dispersibility of (A), further preventing uneven distribution and aggregation, and further improving the low thermal expansion property, the amount is preferably 10 to 220 parts by mass, more preferably 20 to 200 parts by mass, further preferably 30 to 150 parts by mass, and further more preferably 40 to 120 parts by mass, relative to 100 parts by mass of the resin solid content in the resin composition.

[0080] In addition, in this embodiment, from the perspective of miniaturization of the circuit, high capacitance of the capacitor, and miniaturization of high-frequency electrical components, a filler having a high dielectric constant can be used as the filler (B). Examples of such fillers include TiO 2 MgSiO 4 MgTiO 3 、ZnTiO 3 、ZnTiO 4 、CaTiO 3 、SrTiO 3 、SrZrO 3 , BaTi 2 O 5 , Ba 2 Ti9 O 20 、Ba(Ti,Sn) 9 O 20 、ZrTiO 4 、(Zr,Sn)TiO 4 、BaNd 2 Ti 5 O 14 、BaSmTiO 14 、Bi 2 O 3 -BaO-Nd 2 O 3 -TiO 2 ,La 2 Ti 2 O 7 、BaTiO 3 、Ba(Ti,Zr)O 3 , and (Ba,Sr)TiO 3 , and metal particles subjected to insulation treatment of metals such as gold, silver, palladium, copper, nickel, iron, cobalt, zinc, Mn-Mg-Zn, Ni-Zn, Mn-Zn, carbonyl iron, Fe-Si, Fe-Al-Si, and Fe-Ni. These fillers (B) can be used alone or in combination of two or more.

[0081] <Thermosetting resin (C)>

[0082] The resin composition of the present embodiment includes a thermosetting resin (C). The thermosetting compound (C) is not particularly limited as long as it is a thermosetting resin or compound. The thermosetting resin (C) can be used alone or in combination of two or more.

[0083] As the thermosetting resin (C), BaTi 4 O 9 From the perspective of obtaining a resin composition having excellent thermal properties (low thermal expansion coefficient and high glass transition temperature) and dielectric properties (low dielectric loss tangent) by well dispersing (A) and the filler (B), it is preferred that the resin composition contain at least one selected from the group consisting of cyanate compounds, maleimide compounds, epoxy compounds, phenol compounds, alkenyl-substituted nadic imide compounds, oxetane resins, benzoxazine compounds, and compounds having a polymerizable unsaturated group, more preferably contain at least one selected from the group consisting of maleimide compounds, cyanate compounds, phenol compounds, and epoxy compounds, and further preferably contain at least one selected from the group consisting of maleimide compounds, cyanate compounds, and epoxy compounds.

[0084] Regarding the content of the thermosetting resin (C), the content of BaTi4 O 9 In order to obtain a resin composition having better thermal properties (low thermal expansion coefficient and high glass transition temperature) and dielectric properties (low dielectric loss tangent), the resin composition is preferably BaTi. 4 O 9 The total amount of (A) and the filler (B) is preferably 30 to 95 parts by mass, more preferably 35 to 85 parts by mass, further preferably 35 to 80 parts by mass, and still further preferably 45 to 80 parts by mass, based on 100 parts by mass of the total amount.

[0085] (Cyanate ester compound)

[0086] As the cyanate compound, any known one can be suitably used as long as it is a compound having a cyano group (also referred to as "cyanate group" or "cyanate group") directly bonded to two or more aromatic rings in one molecule. The cyanate compound can be used alone or in combination of two or more.

[0087] Examples of such cyanate compounds include phenol novolac cyanate compounds, naphthol aralkyl cyanate compounds, naphthol ether cyanate compounds, xylene resin cyanate compounds, bisphenol M cyanate compounds, bisphenol A cyanate compounds, diallyl bisphenol A cyanate compounds, bisphenol E cyanate compounds, bisphenol F cyanate compounds, biphenyl aralkyl cyanate compounds, bis(3,3-dimethyl-4-cyanoxyphenyl) methane, 1,3-dicyanobenzene, 1,4-dicyanobenzene, 1,3,5-tricyanobenzene, 1,3-dicyanonaphthalene, 1,4-dicyanonaphthalene, 1,6-dicyanonaphthalene, 1,8-dicyanonaphthalene, 2,6-dicyanonaphthalene, 2,7-dicyanonaphthalene, 1,3,6-tricyanonaphthalene, 4,4'-dicyanobiphenyl, bis(4-cyanophenyl)ether, bis(4-cyanophenyl)sulfide, and bis(4-cyanophenyl)sulfone. In addition, these cyanate compounds may be prepolymers or polymers of cyanate compounds.

[0088] Among these, from BaTi 4 O 9From the perspective of better dispersion of (A) and the filler (B), obtaining a resin composition having more excellent thermal properties (low thermal expansion coefficient and high glass transition temperature) and dielectric properties (low dielectric loss tangent), and further obtaining an insulating layer having suitable surface hardness, the cyanate ester compound preferably includes one or more selected from the group consisting of phenol novolac type cyanate ester compounds, naphthol aralkyl type cyanate ester compounds, naphthol ether type cyanate ester compounds, xylene resin type cyanate ester compounds, bisphenol M type cyanate ester compounds, bisphenol A type cyanate ester compounds, diallyl bisphenol A type cyanate ester compounds, bisphenol E type cyanate ester compounds, bisphenol F type cyanate ester compounds, and biphenyl aralkyl type cyanate ester compounds, and prepolymers or polymers of these cyanate ester compounds, and more preferably a naphthol aralkyl type cyanate ester compound.

[0089] As such a naphthol aralkyl type cyanate ester compound, a compound represented by formula (1) is more preferable.

[0090]

[0091] In formula (1), R 3 Each independently represents a hydrogen atom or a methyl group, and a hydrogen atom is preferred. In formula (1), n3 is an integer greater than or equal to 1, preferably an integer of 1 to 20, and more preferably an integer of 1 to 10.

[0092] As the bisphenol A type cyanate ester compound, one or more selected from the group consisting of 2,2-bis(4-cyanophenyl)propane and a prepolymer of 2,2-bis(4-cyanophenyl)propane can be used.

[0093] As such a bisphenol A type cyanate compound, commercially available products can be used, for example, Primaset (registered trademark) BADCy (trade name, Lonza KK., 2,2-bis(4-cyanophenyl)propane, cyanate group equivalent: 139 g / eq.) and CA210 (trade name, Mitsubishi Gas Chemical Co., Ltd., a prepolymer of 2,2-bis(4-cyanophenyl)propane, cyanate group equivalent: 139 g / eq.).

[0094] These cyanate compounds can be produced according to known methods. As a specific production method, for example, the method described in Japanese Patent Application Laid-Open No. 2017-195334 (particularly paragraphs 0052 to 0057) can be cited.

[0095] The content of the cyanate compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solid components in the resin composition. The content of the cyanate compound can be 10 to 70 parts by mass, 15 to 65 parts by mass, or 20 to 60 parts by mass relative to a total of 100 parts by mass of the resin solid components in the resin composition. The content of the cyanate compound is within the above range, thereby having a tendency to be more excellent in heat resistance, low dielectric loss tangent, etc.

[0096] (Maleimide compound)

[0097] As long as the maleimide compound has one or more maleimide groups in one molecule, known substances can be suitably used, and the type thereof is not particularly limited. The number of maleimide groups in one molecule of the maleimide compound is 1 or more, preferably 2 or more. The maleimide compound can be used alone or in combination of two or more.

[0098] Examples of the maleimide compound include N-phenylmaleimide, N-hydroxyphenylmaleimide, bis(4-maleimidephenyl)methane, 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane, bis(3,5-dimethyl-4-maleimidephenyl)methane, bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, bis(3,5-diethyl-4-maleimidephenyl)methane, a maleimide compound represented by formula (2), a maleimide compound represented by formula (3), a maleimide compound represented by formula (4), prepolymers of these maleimide compounds, and prepolymers of the above maleimide compounds and amine compounds.

[0099] Among these, from BaTi 4 O 9From the perspective of obtaining a resin composition having better thermal properties (low thermal expansion coefficient and high glass transition temperature) and dielectric properties (low dielectric loss tangent) by better compatibility between (A) and filler (B), it is preferred that the resin composition contains at least one selected from the group consisting of bis(4-maleimidephenyl)methane, 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane, bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, a maleimide compound represented by formula (2), a maleimide compound represented by formula (3), and a maleimide compound represented by formula (4), and it is more preferred that the resin composition contains at least one selected from the group consisting of 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane and a maleimide compound represented by formula (3). From the perspective of obtaining a resin composition having a further lower dielectric loss tangent, it is also preferred that the maleimide compound represented by formula (4) is contained.

[0100]

[0101] In formula (2), R 1 Each independently represents a hydrogen atom or a methyl group, and n1 is an integer of 1-10.

[0102]

[0103] In formula (3), R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a phenyl group, and n2 is an average value, which represents 1 <n2≤5。

[0104] Examples of the alkyl group having 1 to 5 carbon atoms include linear alkyl groups such as methyl, ethyl, propyl, butyl, and pentyl; and branched alkyl groups such as isopropyl, isobutyl, sec-butyl, and tert-butyl.

[0105]

[0106] In formula (4), Ra each independently represents a hydrogen atom, an alkyl group, an alkoxy group or an alkylthio group having 1 to 10 carbon atoms, an aryl group, an aryloxy group or an arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a nitro group, a hydroxyl group or a mercapto group. q represents an integer of 0 to 4. When q is an integer of 2 to 4, Ra may be the same or different in the same ring. Rb each independently represents a hydrogen atom, an alkyl group, an alkoxy group or an alkylthio group having 1 to 10 carbon atoms, an aryl group, an aryloxy group or an arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a hydroxyl group or a mercapto group. r represents an integer of 0 to 3. When r is 2 or 3, Rb may be the same or different in the same ring. n represents the average number of repeating units, and represents a value of 0.95 to 10.0.

[0107] Examples of the alkyl group having 1 to 10 carbon atoms include, in addition to the alkyl group having 1 to 5 carbon atoms exemplified above, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, isononyl and n-decyl.

[0108] Examples of the alkoxy group having 1 to 10 carbon atoms include a methoxy group, an ethoxy group, an n-propoxy group, an n-butoxy group, an n-pentyloxy group, and an n-hexyloxy group.

[0109] Examples of the alkylthio group having 1 to 10 carbon atoms include a methylthio group and an ethylthio group.

[0110] Examples of the aryl group having 6 to 10 carbon atoms include phenyl, cyclohexylphenyl, phenolic, cyanophenyl, nitrophenyl, naphthyl, biphenylyl, anthracenyl, naphthacene, anthracenyl, pyrenyl, perylenyl, pentacene, benzopyrenyl, chrysyl, pyrenyl, and triphenylenyl.

[0111] Examples of the aryloxy group having 6 to 10 carbon atoms include a phenoxy group and a p-tolyloxy group.

[0112] Examples of the arylthio group having 6 to 10 carbon atoms include a phenylthio group and a p-tolylthio group.

[0113] Examples of the cycloalkyl group having 3 to 10 carbon atoms include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl.

[0114] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0115] In the formula (4), Ra is preferably each independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms.

[0116] In formula (4), q is preferably 2 or 3, and more preferably 2.

[0117] In formula (4), preferably all Rb are hydrogen atoms. Also, preferably, r is an integer of 1 to 3, and each Rb is independently a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms.

[0118] The maleimide compound represented by formula (4) can be produced according to a known method. As a specific production method, for example, the method described in WO2020 / 217679 can be cited.

[0119] The maleimide compound may be a commercial product or a product manufactured by a known method. Commercial products of the maleimide compound include, for example, BMI-70, BMI-80 (2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane), and BMI-1000P (the above, trade names, K.I Chemical Industry Co., LTD.); BMI-3000, BMI-4000, BMI-5100, BMI-7000, and BMI-2300 (maleimide compound represented by the above formula (2)) (the above, trade names, Yamato Chemical Industry Co., Ltd.); MIR-3000-MT (trade name, maleimide compound represented by the above formula (3), Nippon Kayaku Co., Ltd.); NE-X-9470S (trade name, maleimide compound represented by the above formula (4), DIC Corporation), etc.

[0120] The content of the maleimide compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solids in the resin composition. The content of the maleimide compound can be 10 to 70 parts by mass, 15 to 65 parts by mass, or 20 to 60 parts by mass relative to a total of 100 parts by mass of the resin solids in the resin composition. By having the content of the maleimide compound within the above range, there is a tendency to have better heat resistance, etc.

[0121] (Epoxides)

[0122] As long as the epoxy compound has one or more epoxy groups in one molecule, known epoxy compounds can be used appropriately, and the type thereof is not particularly limited. The number of epoxy groups in one molecule of the epoxy compound is 1 or more, preferably 2 or more. The epoxy compound can be used alone or in combination of two or more.

[0123] As the epoxy compound, conventionally known epoxy compounds and epoxy resins can be used. For example, biphenyl aralkyl epoxy resins, naphthalene epoxy resins, binaphthyl epoxy resins, multifunctional phenol epoxy resins, naphthyl ether epoxy resins, phenol aralkyl epoxy resins, phenol novolac epoxy resins, cresol novolac epoxy resins, xylene novolac epoxy resins, naphthalene skeleton modified novolac epoxy resins, dicyclopentadiene novolac epoxy resins, biphenyl novolac epoxy resins, phenol aralkyl novolac epoxy resins, naphthol aralkyl novolac epoxy resins, aralkyl novolac epoxy resins, aromatic hydrocarbon formaldehyde epoxy compounds, anthraquinone epoxy compounds, anthracene epoxy resins, naphthol aralkyl epoxy compounds ... aralkyl novolac epoxy resins, aromatic hydrocarbon formaldehyde epoxy compounds, anthraquinone epoxy compounds, anthracene epoxy resins, Cyclopentadiene epoxy resins, Xylok epoxy compounds, bisphenol A epoxy resins, bisphenol E epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, bisphenol A novolac epoxy resins, phenol epoxy compounds, biphenyl epoxy resins, aralkyl novolac epoxy resins, triazine skeleton epoxy compounds, triglycidyl isocyanurate, alicyclic epoxy resins, polyol epoxy resins, glycidylamine, glycidyl ester resins, butadiene skeleton-containing epoxy resins, etc., compounds obtained by epoxidizing double bonds of double-bond compounds such as butadiene, and compounds obtained by reacting hydroxyl-containing silicone resins with epichlorohydrin, etc.

[0124] Among these, from BaTi 4 O 9 From the perspective of better dispersion of (A) and filler (B) to obtain a resin composition having more excellent thermal properties (low thermal expansion coefficient and high glass transition temperature) and dielectric properties (low dielectric loss tangent), it is preferred to contain one or more selected from the group consisting of biphenyl aralkyl type epoxy resins, naphthalene type epoxy resins, naphthyl ether type epoxy resins, and butadiene skeleton-containing epoxy resins, and more preferably one or more selected from the group consisting of naphthyl ether type epoxy resins and biphenyl aralkyl type epoxy resins.

[0125] The biphenyl aralkyl type epoxy resin is preferably a compound represented by the following formula (5).

[0126]

[0127] In the formula (5), ka represents an integer of 1 or more, preferably an integer of 1-20, and more preferably an integer of 1-10.

[0128] As the biphenyl aralkyl type epoxy resin, commercial products can be used, and products manufactured by a known method can also be used. Commercial products include, for example, NC-3000, NC-3000L, NC-3000H, and NC-3000FH (compounds represented by the above formula (5), wherein ka is an integer of 1 to 10) (the above, trade names, Nippon Kayaku Co., Ltd.) and the like.

[0129] As the naphthalene type epoxy resin, a compound represented by the following formula (6) is preferred.

[0130]

[0131] In formula (6), R 3b Each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms (e.g., methyl or ethyl), an aralkyl group, a benzyl group, a naphthyl group, a naphthyl group containing at least one glycidyloxy group, or a naphthylmethyl group containing at least one glycidyloxy group, and n represents an integer greater than 0 (e.g., 0 to 2).

[0132] Examples of commercially available products of the compound represented by the above formula (6) include EPICLON (registered trademark) EXA-4032-70M (where n=0, R in the above formula (6) is 3b are all hydrogen atoms), EPICLON (registered trademark) HP-4710 (in the above formula (6), n=0, R 3b is a naphthylmethyl group containing at least one glycidyloxy group) (the above, trade name, DIC Corporation).

[0133] As the naphthyl ether type epoxy resin, a bifunctional epoxy compound represented by the following formula (7) or a polyfunctional epoxy compound represented by the following formula (8), or a mixture thereof is preferred.

[0134]

[0135] In formula (7), R 13 Each independently represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms (for example, a methyl group or an ethyl group), or an alkenyl group having 2 to 3 carbon atoms (for example, a vinyl group, an allyl group, or a propenyl group).

[0136]

[0137] In formula (8), R 14 Each independently represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms (for example, a methyl group or an ethyl group), or an alkenyl group having 2 to 3 carbon atoms (for example, a vinyl group, an allyl group, or a propenyl group).

[0138] The naphthyl ether type epoxy resin may be a commercial product or a product manufactured by a known method. Examples of commercial products include HP-6000, EXA-7300, EXA-7310, EXA-7311, EXA-7311L, EXA7311-G3, EXA7311-G4, EXA-7311G4S, and EXA-7311G5 (above, trade names, DIC Corporation). Among these, HP-6000 (trade name) is preferred.

[0139] The butadiene skeleton-containing epoxy resin may be any epoxy resin having a butadiene skeleton and an epoxy group in the molecule. Examples of such a resin include butadiene skeleton-containing epoxy resins represented by the following formulas (9) to (11).

[0140]

[0141] In formula (9), X represents an integer of 1 to 100, and Y represents an integer of 0 to 100.

[0142]

[0143] In formula (10), R represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, a and b each independently represent an integer of 1 to 100, and c and d each independently represent an integer of 0 to 100. Examples of the alkyl group include methyl, ethyl, propyl, and butyl groups.

[0144]

[0145] In the formula (11), e represents an integer of 24 to 35, and f represents an integer of 8 to 11.

[0146] The epoxy resin containing a butadiene skeleton may be a commercial product or a product produced by a known method. Examples of commercial products include R-15EPT and R-45EPT (compounds in the above formula (9) where X=50 and Y=0) (the above trade names, Nagase ChemteX Corporation); EPOLEAD (registered trademark) PB3600 and PB4700 (the above trade names, Daicel Corporation); and Nippon Polybutadiene E-1000-3.5 (trade name, Shin Nippon Petrochemical Co., Ltd.).

[0147] The content of the epoxy compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass, relative to a total of 100 parts by mass of the resin solid components in the resin composition. The content of the epoxy compound can be 10 to 70 parts by mass, 15 to 65 parts by mass, or 20 to 60 parts by mass relative to a total of 100 parts by mass of the resin solid components in the resin composition. When the content of the epoxy compound is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0148] (Phenol compounds)

[0149] As the phenol compound, any known phenol compound may be suitably used as long as it has two or more phenolic hydroxyl groups in one molecule, and the type thereof is not particularly limited. The phenol compound may be used alone or in combination of two or more.

[0150] As phenolic compounds, for example, cresol novolac type phenolic resin, biphenyl aralkyl type phenolic resin represented by formula (12), naphthol aralkyl type phenolic resin represented by formula (13), aminotriazine novolac type phenolic resin, naphthalene type phenolic resin, phenol novolac resin, alkylphenol novolac resin, bisphenol A type novolac resin, dicyclopentadiene type phenolic resin, Xylok type phenolic resin, terpene modified phenolic resin, and polyvinylphenols can be cited.

[0151] Among these, from the perspective of obtaining excellent moldability and surface hardness, preferred are cresol novolac type phenolic resins, biphenyl aralkyl type phenolic resins represented by formula (12), naphthol aralkyl type phenolic resins represented by formula (13), aminotriazine novolac type phenolic resins, and naphthalene type phenolic resins, and more preferred are biphenyl aralkyl type phenolic resins represented by formula (12) and naphthol aralkyl type phenolic resins represented by formula (13).

[0152]

[0153] In formula (12), R 4 Each independently represents a hydrogen atom or a methyl group, and n4 is an integer of 1-10.

[0154]

[0155] In formula (13), R 5 Each independently represents a hydrogen atom or a methyl group, and n5 is an integer of 1-10.

[0156] The content of the phenolic compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solid content of the resin composition. When the content of the phenolic compound is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0157] (Alkenyl-substituted nadic imide compound)

[0158] The alkenyl-substituted nadic acid imide compound is not particularly limited as long as it is a compound having one or more alkenyl-substituted nadic acid imide groups in one molecule. The alkenyl-substituted nadic acid imide compound may be used alone or in combination of two or more.

[0159] Examples of the alkenyl-substituted nadic acid imide compound include compounds represented by the following formula (14).

[0160]

[0161] In formula (14), R 1 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (such as a methyl group or an ethyl group), and R 2 It represents an alkylene group having 1 to 6 carbon atoms, a phenylene group, a biphenylene group, a naphthylene group, or a group represented by the formula (15) or (16).

[0162]

[0163] In formula (15), R 3 represents methylene, isopropylidene, CO, O, S or SO 2 .

[0164]

[0165] In formula (16), R 4 Each independently represents an alkylene group having 1 to 4 carbon atoms or a cycloalkylene group having 5 to 8 carbon atoms.

[0166] The alkenyl-substituted nadic acid imide compound represented by formula (14) may be a commercially available product or a product produced by a known method. Examples of commercially available products include BANI-M and BANI-X (these are trade names, Maruzen Petrochemical Co., Ltd.).

[0167] The content of the alkenyl-substituted nadic acid imide compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solid content of the resin composition. When the content of the alkenyl-substituted nadic acid imide compound is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0168] (Oxetane resin)

[0169] The oxetane resin is not particularly limited, and generally known oxetane resins can be used. The oxetane resin can be used alone or in combination of two or more.

[0170] Examples of the oxetane resin include oxetane, 2-methyloxetane, 2,2-dimethyloxetane, 3-methyloxetane, alkyloxetanes such as 3,3-dimethyloxetane, 3-methyl-3-methoxymethyloxetane, 3,3-bis(trifluoromethyl)perfluorooxetane, 2-chloromethyloxetane, 3,3-bis(chloromethyl)oxetane, biphenyl-type oxetane, OXT-101 (trade name, Toagosei Co., Ltd.), and OXT-121 (trade name, Toagosei Co., Ltd.).

[0171] The content of the oxetane resin is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solid content of the resin composition. When the content of the oxetane resin is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0172] (Benzoxazine compounds)

[0173] The benzoxazine compound is not particularly limited as long as it has two or more dihydrobenzoxazine rings in one molecule, and generally known compounds can be used. The benzoxazine compound can be used alone or in combination of two or more.

[0174] Examples of the benzoxazine compound include bisphenol A-type benzoxazine BA-BXZ, bisphenol F-type benzoxazine BF-BXZ, and bisphenol S-type benzoxazine BS-BXZ (the above, trade names, Konishi Chemical Industries, Ltd.).

[0175] The content of the benzoxazine compound is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to 100 parts by mass of the total resin solid content of the resin composition. When the content of the benzoxazine compound is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0176] (Compound having a polymerizable unsaturated group)

[0177] The compound having a polymerizable unsaturated group is not particularly limited, and generally known compounds can be used. The compound having a polymerizable unsaturated group can be used alone or in combination of two or more.

[0178] Examples of the compound having a polymerizable unsaturated group include vinyl compounds such as ethylene, propylene, styrene, divinylbenzene, and divinylbiphenyl; (meth)acrylates of monohydric or polyhydric alcohols such as methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate; epoxy (meth)acrylates such as bisphenol A epoxy (meth)acrylate and bisphenol F epoxy (meth)acrylate; and benzocyclobutene resins.

[0179] The content of the compound having a polymerizable unsaturated group is preferably 1 to 99 parts by mass, more preferably 3 to 90 parts by mass, further preferably 4 to 85 parts by mass, and further more preferably 5 to 80 parts by mass relative to a total of 100 parts by mass of the resin solid content of the resin composition. When the content of the compound having a polymerizable unsaturated group is within the above range, there is a tendency for the adhesiveness, flexibility, etc. to be more excellent.

[0180] <Silane coupling agent>

[0181] The resin composition of this embodiment may further contain a silane coupling agent. The resin composition contains a silane coupling agent, thereby 4 O 9 The dispersibility of (A) and the filler (B) is further improved, and the bonding strength between each component contained in the resin composition and the substrate described below tends to be further improved. The silane coupling agent can be used alone or in combination of two or more.

[0182] As silane coupling agent, it is not particularly limited, and silane coupling agent commonly used for surface treatment of inorganic substances can be used. For example, aminosilane compounds (such as γ-aminopropyl triethoxysilane, N-β-(aminoethyl)-γ-aminopropyl trimethoxysilane, etc.), epoxy silane compounds (such as γ-glycidoxypropyl trimethoxysilane, etc.), acrylic silane compounds (such as γ-acryloxypropyl trimethoxysilane, etc.), cationic silane compounds (such as N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyl trimethoxysilane hydrochloride, etc.), styryl silane compounds, phenyl silane compounds, etc. can be cited. Silane coupling agent can be used alone or in combination of two or more. Among these, the silane coupling agent is preferably an epoxy silane compound. Examples of the epoxysilane-based compound include KBM-403, KBM-303, KBM-402, and KBE-403 (these are trade names, Shin-Etsu Chemical Co., Ltd.).

[0183] The content of the silane coupling agent is not particularly limited, but may be 0.1 to 5.0 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.

[0184] <Wetting and dispersing agent>

[0185] The resin composition of this embodiment may further contain a wetting dispersant. The resin composition contains a wetting dispersant, so that the dispersibility of the filler tends to be further improved. The wetting dispersant can be used alone or in combination of two or more.

[0186] The wetting dispersant may be any known dispersant (dispersion stabilizer) for dispersing fillers, and examples thereof include DISPER BYK (registered trademark)-110, 111, 118, 180, 161, 2009, 2152, 2155, W996, W9010, and W903 (these are trade names, BYK Chemie Japan KK).

[0187] The content of the wetting and dispersing agent is not particularly limited, but is preferably 0.5 parts by mass or more and 5.0 parts by mass or less relative to 100 parts by mass of the resin solid content in the resin composition.

[0188] <Curing accelerator>

[0189] The resin composition of the present embodiment may further contain a curing accelerator. The curing accelerator may be used alone or in combination of two or more.

[0190] Examples of the curing accelerator include imidazoles such as triphenylimidazole; organic peroxides such as benzoyl peroxide, lauroyl peroxide, acetyl peroxide, p-chlorobenzoyl peroxide, and di-tert-butyl diperoxyphthalate; azo compounds such as azobisnitrile; N,N-dimethylbenzylamine, N,N-dimethylaniline, N,N-dimethyltoluidine, 2-N-ethylanilinoethanol, tri-n-butylamine, pyridine, quinoline, N-methylmorpholine, triethanolamine, triethylenediamine, tetramethylbutylene diamine, Tertiary amines such as N-methylpiperidine; phenols such as phenol, xylenol, cresol, resorcinol, and catechol; organic metal salts such as lead naphthenate, lead stearate, zinc naphthenate, zinc octoate, manganese octoate, tin oleate, dibutyltin maleate, manganese naphthenate, cobalt naphthenate, and ferric acetylacetonate; those obtained by dissolving these organic metal salts in hydroxyl-containing compounds such as phenol and bisphenol; inorganic metal salts such as tin chloride, zinc chloride, and aluminum chloride; organic tin compounds such as dioctyltin oxide, other alkyl tins, and alkyl tin oxides, etc. Among these, triphenylimidazole has a tendency to promote the curing reaction and further increase the glass transition temperature, so it is particularly preferred.

[0191] <Solvents>

[0192] The resin composition of the present embodiment may further contain a solvent. The resin composition includes a solvent, thereby having a viscosity drop during the preparation of the resin composition, further improving the handling property (operability), and further improving the impregnation property of the substrate. The solvent can be used alone or in combination of two or more.

[0193] The solvent is not particularly limited as long as it can dissolve part or all of the components in the resin composition, and examples thereof include ketones (acetone, methyl ethyl ketone, etc.), aromatic hydrocarbons (such as toluene, xylene, etc.), amides (such as dimethyl formaldehyde, etc.), propylene glycol monomethyl ether and its acetate, etc.

[0194] <Other ingredients>

[0195] The resin composition of the present embodiment may contain components other than the above within the range that does not impair the desired properties. As flame retardant compounds, for example, 4,4'-dibromobiphenyl bromide compounds; nitrogen-containing compounds such as phosphate esters, melamine phosphate, melamine, and benzoguanamine; silicon compounds, etc. In addition, various additives include ultraviolet absorbers, antioxidants, photopolymerization initiators, fluorescent whitening agents, photosensitizers, dyes, pigments, thickeners, lubricants, defoamers, dispersants, leveling agents, glossing agents, and polymerization inhibitors.

[0196] [Method for producing resin composition]

[0197] The method for producing the resin composition of the present embodiment can be exemplified by the following method: BaTi 4 O9 (A), filler (B), thermosetting resin (C), and the above components as needed are mixed and stirred thoroughly. At this time, in order to make each component dissolve or disperse evenly, known treatments such as stirring, mixing, and kneading can be performed. Specifically, a stirring tank equipped with a stirrer with appropriate stirring capacity is used for stirring and dispersing treatment, thereby improving the BaTi content in the resin composition. 4 O 9 The above stirring, mixing and kneading treatment can be appropriately carried out using, for example, a mixing device such as a ball mill or a bead mill, or a known device such as a mixing device of a revolution type or an autogenous type.

[0198] In addition, when preparing the resin composition, a solvent may be used as needed to prepare the resin varnish. The type of the solvent is not particularly limited as long as it can dissolve the resin in the resin composition. Specific examples thereof are as described above.

[0199] 〔use〕

[0200] The resin composition of the present embodiment can be used, for example, as a raw material for a cured product, a prepreg, a film-like underfill material, a resin sheet, a laminate, a build-up material, a non-conductive film, a metal foil-clad laminate, a printed circuit board, and a fiber-reinforced composite material, or in the manufacture of a semiconductor device. These are described below.

[0201] 〔Cured product〕

[0202] The cured product is obtained by curing the resin composition of the present embodiment. As a method for producing the cured product, for example, the resin composition of the present embodiment can be melted or dissolved in a solvent, poured into a mold, and cured under normal conditions using heat, light, etc., to obtain the cured product. In the case of thermal curing, the curing temperature is preferably within the range of 120 to 300° C. from the viewpoint of effectively promoting curing and preventing degradation of the obtained cured product.

[0203] 〔Prepreg〕

[0204] The prepreg of the present embodiment includes: a substrate; and, a resin composition of the present embodiment impregnated or coated on the substrate. The prepreg of the present embodiment can be obtained, for example, as follows: after impregnating or coating the substrate with the resin composition of the present embodiment (for example, in an uncured state (A stage)), the prepreg is semi-cured by drying at 120 to 220°C for about 2 to 15 minutes. In this case, the amount of the resin composition (including the cured product of the resin composition) attached to the substrate, that is, the amount of the resin composition (including BaTi 4 O 9(A) and filler (B)) are preferably in the range of 20 to 99 mass %.

[0205] As substrate, as long as it is a substrate for various printed circuit board materials, there is no particular limitation. As the material of substrate, for example, glass fiber (such as E-glass, D-glass, L-glass, S-glass, T-glass, Q-glass, UN-glass, NE-glass and spherical glass, etc.), inorganic fibers other than glass fiber (such as quartz, etc.), organic fibers (such as polyimide, polyamide, polyester, liquid crystal polyester and polytetrafluoroethylene, etc.) can be cited. As the form of substrate, there is no particular limitation, and woven fabric, non-woven fabric, roving, short glass fiber mat and surface mat, etc. can be cited. These substrates can be used alone or in combination with more than two kinds. Among these substrates, from the viewpoint of dimensional stability, it is preferred to implement super fiber opening treatment and hole filling treatment of woven fabrics, from the viewpoint of moisture absorption and heat resistance, preferably epoxy silane treatment and amino silane treatment, etc., using silane coupling agents, etc., to carry out surface treatment of glass woven fabrics. From the aspect of having excellent dielectric properties, glass fibers such as E-glass, L-glass, NE-glass and Q-glass are preferred.

[0206] 〔Resin sheet〕

[0207] The resin sheet of the present embodiment includes the resin composition of the present embodiment. The resin sheet can be formed into a resin sheet with a support body including a support body and a layer formed by the resin composition of the present embodiment disposed on the surface of the support body. The resin sheet can be used as a laminated film or a dry film solder resist. There is no particular limitation on the method for manufacturing the resin sheet, and for example, the following method can be cited: a solution in which the resin composition of the present embodiment is dissolved in a solvent is applied (coated) to a support body and dried to obtain a resin sheet.

[0208] Examples of the support include polyethylene film, polypropylene film, polycarbonate film, polyethylene terephthalate film, ethylene tetrafluoroethylene copolymer film, release film having a release agent coated on the surface of these films, organic film substrates such as polyimide film, conductor foil such as copper foil and aluminum foil, glass plate, SUS plate, FRP and the like, but are not particularly limited.

[0209] As a coating method (applying method), for example, the following method can be cited: a solution in which the resin composition of the present embodiment is dissolved in a solvent is applied to a support using a rod coater, a die coater, a scraper, a Baker applicator, etc. In addition, after drying, the support can be peeled off or etched from a resin sheet with a support in which a support and a resin composition are stacked, thereby forming a single-layer sheet (resin sheet). It should be noted that a solution in which the resin composition of the present embodiment is dissolved in a solvent is supplied to a mold having a sheet-shaped cavity and dried to form a sheet, so that a single-layer sheet (resin sheet) can be obtained without using a support.

[0210] It should be noted that in the preparation of the single-layer sheet or the resin sheet with a support described in the present embodiment, the drying conditions for removing the solvent are not particularly limited. From the viewpoint that the solvent in the resin composition is easily removed and the curing during drying is suppressed, it is preferably 1 to 90 minutes at a temperature of 20 to 200°C. In addition, in the single-layer sheet or the resin sheet with a support, the resin composition can also be used in an uncured state in which only the solvent is dried, or it can be used in a semi-cured (B-stage) state as needed. Furthermore, the thickness of the resin layer of the single-layer sheet or the resin sheet with a support of the present embodiment can be adjusted according to the concentration of the solution of the resin composition of the present embodiment and the coating thickness, and is not particularly limited. From the viewpoint that the solvent becomes easy to remove during drying, it is preferably 0.1 to 500 μm.

[0211] 〔Laminated board〕

[0212] The laminated plate of the present embodiment includes one or more selected from the group consisting of the prepreg and the resin sheet of the present embodiment. For prepreg and resin sheet, when more than two are stacked, the resin composition used in each prepreg and resin sheet may be the same or different. In addition, when both prepreg and resin sheet are used, the resin composition used in them may be the same or different. In the laminated plate of the present embodiment, one or more selected from the group consisting of prepreg and resin sheet may be in a semi-cured state (B stage) or in a fully cured state (C stage). The semi-cured state (B stage) means that the components contained in the resin composition do not actively start to react (curing), but the resin composition is in a dry state, that is, the state in which the solvent is volatilized until there is no adhesion, and the state in which the solvent is only volatilized even if it is not heated is not cured. In the present embodiment, the minimum melt viscosity of the semi-cured state (B stage) is usually less than 20000 Pa s. The lower limit of the minimum melt viscosity is, for example, more than 10 Pa s. It should be noted that, in the present embodiment, the minimum melt viscosity is measured by the following method. That is, using 1 g of resin powder collected from the resin composition as a sample, the minimum melt viscosity was measured using a rheometer (ARES-G2 (trade name), TA Instrument). Here, a disposable plate with a plate diameter of 25 mm was used, and the minimum melt viscosity of the resin powder was measured in the range of 40° C. to 180° C., at a heating rate of 2° C. / min, a frequency of 10.0 rad / sec, and a strain of 0.1%.

[0213] [Metal foil-clad laminate]

[0214] The metal foil-clad laminated plate of the present embodiment includes the laminated plate of the present embodiment and a metal foil disposed on one surface or both surfaces of the laminated plate.

[0215] The metal foil-clad laminate may include at least one prepreg according to the present embodiment and a metal foil laminated on one or both surfaces of the prepreg.

[0216] Furthermore, the metal foil-clad laminate may include at least one resin sheet of the present embodiment and a metal foil laminated on one surface or both surfaces of the resin sheet.

[0217] In the metal foil clad laminate of the present embodiment, the resin compositions used in the prepregs and the resin sheets may be the same or different, and when both the prepregs and the resin sheets are used, the resin compositions used in them may be the same or different. In the metal foil clad laminate of the present embodiment, one or more selected from the group consisting of the prepregs and the resin sheets may be in a semi-cured state or in a fully cured state.

[0218] In the metal foil clad laminate of the present embodiment, metal foil is laminated on one or more of the group consisting of the prepreg of the present embodiment and the resin sheet of the present embodiment, wherein the metal foil is preferably laminated in a manner of contacting with the surface of one or more of the group consisting of the prepreg of the present embodiment and the resin sheet of the present embodiment. "Metal foil is laminated in a manner of contacting with the surface of one or more of the group consisting of the prepreg and the resin sheet" means that there is no layer such as an adhesive layer between the prepreg or the resin sheet and the metal foil, and the prepreg or the resin sheet is in direct contact with the metal foil. As a result, there is a tendency that the metal foil peeling strength of the metal foil clad laminate becomes higher, and the insulation reliability of the printed circuit board is improved.

[0219] The metal foil clad laminate of the present embodiment may have: one or more prepregs and / or resin sheets of the present embodiment overlapped, and metal foil disposed on one or both sides of the prepregs and / or resin sheets. As a method for manufacturing the metal foil clad laminate of the present embodiment, for example, the following method can be cited: overlap one or more prepregs and / or resin sheets of the present embodiment, and configure metal foil on one or both sides thereof and perform laminate molding. As a molding method, the method commonly used when molding laminates and multilayer boards for printed circuit boards can be cited. In more detail, the following method can be cited: use a multi-stage press, a multi-stage vacuum press, a continuous molding machine, an autoclave molding machine, etc., at a temperature of about 180 to 350°C, a heating time of about 100 to 300 minutes, and a surface pressure of 20 to 100 kgf / cm 2 The left and right layers are stacked and formed.

[0220] In addition, by combining the prepreg and / or resin sheet of the present embodiment with a circuit board for the inner layer prepared separately and performing stacking molding, a multilayer board can also be formed. As a manufacturing method for a multilayer board, for example, a copper foil with a thickness of about 35 μm is configured on both sides of the prepreg and / or resin sheet of the present embodiment that overlaps more than one sheet, and stacking molding is performed by the above-mentioned molding method. After forming a copper foil-clad laminate, an inner layer circuit is formed, and a blackening treatment is performed on the circuit to form an inner layer circuit board. After that, the inner layer circuit board and the prepreg and / or resin sheet of the present embodiment are alternately configured with one sheet each, and copper foil is further configured in the outermost layer. Under the above conditions, preferably stacking molding is performed under vacuum, so that a multilayer board can be made. The metal foil-clad laminate of the present embodiment can be suitable for use as a printed circuit board.

[0221] (metal foil)

[0222] The metal foil is not particularly limited, and examples thereof include gold foil, silver foil, copper foil, tin foil, nickel foil, and aluminum foil. Among them, copper foil is preferred. The copper foil is not particularly limited as long as it is a material commonly used for printed circuit boards, and examples thereof include rolled copper foil and electrolytic copper foil. Among them, electrolytic copper foil is preferred from the viewpoint of copper foil peel strength and fine wiring formation. The thickness of the copper foil is not particularly limited, and may be about 1.5 to 70 μm.

[0223] 〔Printed circuit board〕

[0224] The printed circuit board of the present embodiment has: an insulating layer, and a conductor layer disposed on one or both sides of the insulating layer, and the insulating layer comprises a cured product of the resin composition of the present embodiment. The insulating layer preferably comprises at least one of a layer (a layer comprising a cured product) formed by the resin composition of the present embodiment and a layer (a layer comprising a cured product) formed by a prepreg. Such a printed circuit board can be manufactured according to a conventional method, and its manufacturing method is not particularly limited, for example, it can be manufactured using the above-mentioned metal foil-clad laminate. Below, an example of a method for manufacturing a printed circuit board is shown.

[0225] First, prepare the above-mentioned metal foil-clad laminate. Then, the surface of the metal foil-clad laminate is subjected to etching treatment to form the inner layer circuit, and the inner layer substrate is made. The inner layer circuit surface of the inner layer substrate is subjected to surface treatment for improving the bonding strength as needed, and then the required number of prepregs are overlapped on the inner layer circuit surface, and the metal foil for the outer layer circuit is further laminated on its outside, and heated and pressed and integrally formed. In this way, between the copper foil for the inner layer circuit and the outer layer circuit, a multilayer laminate having an insulating layer formed with a substrate and a cured product of the resin composition of the present embodiment is manufactured. Then, after the opening processing for through holes and vias is performed on the multilayer laminate, a metal-plated film that conducts the metal foil for the inner layer circuit and the outer layer circuit is formed on the wall surface of the hole, and the metal foil for the outer layer circuit is further subjected to etching treatment to form an outer layer circuit, thereby manufacturing a printed circuit board.

[0226] The printed wiring board obtained in the above-mentioned manufacturing example has an insulating layer and a conductor layer formed on the surface of the insulating layer, and the insulating layer is composed of a cured product of the resin composition of the present embodiment. That is, the prepreg of the present embodiment (comprising a substrate and a cured product of the resin composition of the present embodiment impregnated or coated thereon) and the layer of the resin composition of the metal foil-clad laminate of the present embodiment (a layer comprising a cured product of the resin composition of the present embodiment) are composed of an insulating layer comprising a cured product of the resin composition of the present embodiment.

[0227] 〔Semiconductor devices〕

[0228] The semiconductor device can be manufactured by mounting a semiconductor chip on the conductive part of the printed circuit board of this embodiment. Here, the conductive part is a part of the multilayer printed circuit board that transmits electrical signals, and its position can be the surface or an embedded part. In addition, the semiconductor chip is not particularly limited as long as it is an electrical circuit element made of semiconductor.

[0229] There are no particular limitations on the method of mounting semiconductor chips when manufacturing semiconductor devices as long as the semiconductor chips can function effectively. Specifically, there are wire bonding mounting methods, flip chip mounting methods, mounting methods using a built-in non-bump layer (BBUL), mounting methods using anisotropic conductive film (ACF), and mounting methods using non-conductive film (NCF).

[0230] Example

[0231] Hereinafter, the present embodiment will be described in more detail using examples and comparative examples. The present embodiment is not limited at all by the following examples.

[0232] [Method for measuring average particle size]

[0233] BaTi used as a raw material in Preparation Example 1 4 O 9 , BaTi used in the comparative example 4 O 9 , BaTi in the slurry obtained in Preparation Example 1 4 O 9 , and the average particle size (D50) of the filler (molten spherical silica) are calculated as follows: Using a laser diffraction / scattering particle size distribution measuring device (Microtrack MT3300EXII (trade name), Microtrac Bell Corporation), the particle size distribution is measured according to the laser diffraction / scattering method based on the following measurement conditions, and the calculation is performed.

[0234] (Measurement conditions of laser diffraction / scattering particle size distribution measuring device)

[0235] Solvent: methyl ethyl ketone, solvent refractive index: 1.33, particle refractive index: 2.41 (BaTi 4 O 9 ), 1.45 (molten spherical silica), transmittance: 85±5%.

[0236] [Production Example 1] BaTi 4 O 9 (A) Production of slurry

[0237] In a 50L metal can, place barium titanate (BaTi 4 O9 , average particle size (D50) 2.1μm, BT-149 (trade name), Nippon Chemical Industry Co., Ltd.), methyl ethyl ketone is added in a manner that it becomes 40% by mass in terms of solid content. Then, a wetting dispersant (DISPERBYK (registered trademark) -2155 (trade name), BYK Chemie Japan KK) is added in a manner that it becomes 1 part by mass relative to 100 parts by mass of barium titanate (BT-149, trade name), and stirred at 350rpm for 100 minutes with a stirrer (Three-one motor). Zirconia beads with a particle size of 0.2mm are filled in the grinding chamber in a manner that it becomes 60% by volume relative to the volume of the grinding chamber, and the stirred solution is passed through the filled continuous bead mill (NAM-20 (trade name), AIMEX CORPORATION) at a discharge rate of 8.5L / min for 300 minutes, and stirred together with the zirconium oxide beads in the grinding chamber at a peripheral speed of 11m / sec to obtain BaTi 4 O 9 (A) slurry. It should be noted that the BaTi 4 O 9 The concentration of (A) was 40% by mass in terms of solid content.

[0238] Determination of BaTi in the obtained slurry 4 O 9 The average particle size of (A) was 0.33 μm.

[0239] [Synthesis Example 1] Synthesis of 1-naphthol aralkyl type cyanate compound (SN495V-CN)

[0240] 300 g (1.28 mol in terms of OH group conversion) of 1-naphthol aralkyl type phenol resin (SN495V (trade name), OH group (hydroxyl) equivalent: 236 g / eq., Nippon Steel Chemical Co., Ltd.) and 194.6 g (1.92 mol) of triethylamine (1.5 mol per 1 mol of hydroxyl group) were dissolved in 1800 g of dichloromethane to prepare solution 1. 125.9 g (2.05 mol) of cyanogen chloride (1.6 mol per 1 mol of hydroxyl group), 293.8 g of dichloromethane, 194.5 g (1.92 mol) of 36% hydrochloric acid (1.5 mol per 1 mol of hydroxyl group) and 1205.9 g of water were poured into solution 1 over 30 minutes while stirring and maintaining the liquid temperature at -2 to -0.5°C. After the injection of solution 1 is completed, stir at the same temperature for 30 minutes, and then inject a solution (solution 2) in which 65g (0.64mol) of triethylamine (0.5mol relative to 1mol of hydroxyl group) is dissolved in 65g of dichloromethane over 10 minutes. After the injection of solution 2 is completed, stir at the same temperature for 30 minutes to terminate the reaction. Thereafter, the reaction solution is allowed to stand, the organic phase and the aqueous phase are separated, and the obtained organic phase is washed 5 times with 1300g of water. The conductivity of the wastewater after the fifth washing is 5μS / cm, confirming that the ionic compounds to be removed by washing with water are fully removed. The organic phase after washing is concentrated under reduced pressure, and finally concentrated to dryness at 90°C for 1 hour to obtain the target 1-naphthol aralkyl type cyanate compound (SN495V-CN, cyanate group equivalent: 261g / eq., R in the above formula (1) 3 All of them are hydrogen atoms, n3 is an integer of 1 to 10) (orange viscous material) 331 g. The infrared absorption spectrum of the obtained SN495V-CN showed that -1 The absorption of the cyanate group is shown, and the absorption of the hydroxyl group is not shown.

[0241] [Example 1]

[0242] 48 parts by mass of the 1-naphthol aralkyl type cyanate compound (SN495V-CN) obtained in Synthesis Example 1, 16 parts by mass of 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane (BMI-80 (trade name), K.I Chemical Industry Co., LTD.), 16 parts by mass of a biphenyl aralkyl type maleimide compound (MIR-3000-MT (trade name), Nippon Kayaku Co., Ltd.), 20 parts by mass of a naphthol ether type epoxy resin (HP-6000 (trade name), epoxy equivalent: 250 g / eq., DIC Corporation), and the BaTiO2 obtained in Preparation Example 1 were mixed. 4 O 990 parts by mass (in terms of solid content) of the slurry (A) (solid content concentration 40%), 19 parts by mass of fused spherical silica (average particle size (D50): 1.10 μm, SC4500-SQ (trade name), Admatechs Co., Ltd.), 3 parts by mass of a silane coupling agent (KBM-403 (trade name), Shin-Etsu Chemical Co., Ltd.), 1 part by mass of DISPERBYK (registered trademark)-161 (trade name, BYK Chemie Japan KK) as a wetting and dispersing agent, and 2 parts by mass of DISPERBYK (registered trademark)-111 (trade name, BYK Chemie Japan KK) (total of wetting and dispersing agents: 3 parts by mass) were mixed to obtain a resin varnish (solid content concentration 50% by mass). It should be noted that the BaTi in the resin varnish 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica was 70:30 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0243] The obtained resin varnish was impregnated and applied to E glass cloth, and then heated and dried at 160°C for 10 minutes to obtain a prepreg with a thickness of 0.1 mm. Next, a 12 μm thick electrolytic copper foil (3EC-M3-VLP (trade name), Mitsui Mining & Smelting Co., Ltd.) was placed on the upper and lower surfaces of the obtained prepreg and pressed at a surface pressure of 30 kgf / cm 2 The laminate was then vacuum pressed at 220°C for 120 minutes to produce a 0.1 mm thick metal foil-clad laminate (double-sided copper-clad laminate). The properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The results are shown in Table 1.

[0244] [Example 2]

[0245] A resin varnish (solid content concentration: 50% by mass) was obtained in the same manner as in Example 1 except that 29 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 60:40 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0246] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0247] [Example 3]

[0248] A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 1 except that 40 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 52:48 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0249] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0250] [Example 4]

[0251] A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 1 except that 80 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 35:65 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0252] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0253] [Example 5]

[0254] A resin varnish (solid content concentration: 50% by mass) was obtained in the same manner as in Example 1 except that 103 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9The mixing ratio (content ratio) of (A) and molten spherical silica is 31:69 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0255] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0256] [Example 6]

[0257] The BaTi obtained in Production Example 1 was blended 4 O 9 A resin varnish (solid content concentration of 50% by mass) was obtained in the same manner as in Example 1 except that 180 parts by mass (in terms of solid content) of the slurry (solid content concentration of 40%) of (A) was used instead of 90 parts by mass, and 80 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 52:48 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0258] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0259] [Example 7]

[0260] 48 parts by mass of the 1-naphthol aralkyl type cyanate compound (SN495V-CN) obtained in Synthesis Example 1, 32 parts by mass of a biphenyl aralkyl type maleimide compound (MIR-3000-MT (trade name), Nippon Kayaku Co., Ltd.), 20 parts by mass of a naphthol ether type epoxy resin (HP-6000 (trade name), epoxy equivalent: 250 g / eq., DIC Corporation), and the BaTi obtained in Preparation Example 1 were mixed. 4 O 990 parts by mass (in terms of solid content) of the slurry (A) (solid content concentration 40%), 80 parts by mass of fused spherical silica (average particle size (D50): 1.10 μm, SC4500-SQ (trade name), Admatechs Co., Ltd.), 3 parts by mass of a silane coupling agent (KBM-403 (trade name), Shin-Etsu Chemical Co., Ltd.), 1 part by mass of DISPERBYK (registered trademark)-161 (trade name, BYK Chemie Japan KK) as a wetting and dispersing agent, and 2 parts by mass of DISPERBYK (registered trademark)-111 (trade name, BYK Chemie Japan KK) (total of wetting and dispersing agents: 3 parts by mass) were mixed to obtain a resin varnish (solid content concentration 50% by mass). It should be noted that the BaTi in the resin varnish 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 35:65 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0261] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0262] [Example 8]

[0263] A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 1 except that 20 parts by mass of a biphenyl aralkyl epoxy resin (NC-3000FH (trade name), epoxy equivalent: 328 g / eq., Nippon Kayaku Co., Ltd.) was added instead of 20 parts by mass of a naphthyl ether epoxy resin (HP-6000 (trade name), epoxy equivalent: 250 g / eq., DIC Corporation), and 80 parts by mass of fused spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. It should be noted that the BaTi in the resin varnish 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 35:65 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0264] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. The measurement results are shown in Table 1.

[0265] [Comparative Example 1]

[0266] Compounding barium titanate (BaTi 4 O 9 , average particle size (D50) 2.08 μm, BT-149 (trade name, Nippon Chemical Industry Co., Ltd.) 90 parts by mass was used instead of the BaTi obtained in Preparation Example 1 4 O 9 A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 4 except that 90 parts by mass of the slurry of (A) was added. The mixing ratio (content ratio) of barium titanate and fused spherical silica in the resin varnish was 35:65 (barium titanate: fused spherical silica) by volume ratio.

[0267] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0268] [Comparative Example 2]

[0269] 48 parts by mass of the 1-naphthol aralkyl cyanate compound (SN495V-CN) obtained in Synthesis Example 1, 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane (BMI-80 (trade name), K.I Chemical Industry Co., LTD.), 16 parts by mass of a biphenyl aralkyl type maleimide compound (MIR-3000-MT (trade name), Nippon Kayaku Co., Ltd.), 16 parts by mass of a naphthyl ether type epoxy resin (HP-6000 (trade name), epoxy equivalent: 250 g / eq., DIC Corporation), 20 parts by mass of a fused spherical silica (average particle size (D50): 1.10 μm, SC4500-SQ (trade name), Admatechs Co., Ltd.), 80 parts by mass of a silane coupling agent (KBM-403 (trade name), Shin-Etsu Chemical Co., Ltd.), 1 part by mass of DISPERBYK (registered trademark)-161 (trade name, BYK Chemie Japan KK) as a wetting and dispersing agent, and 1 part by mass of DISPERBYK (registered trademark)-111 (trade name, BYK Chemie Japan KK) and 2 parts by mass (total of wetting dispersants: 3 parts by mass) were mixed to obtain a resin varnish (solid content concentration: 50% by mass).

[0270] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0271] [Comparative Example 3]

[0272] 48 parts by mass of the 1-naphthol aralkyl type cyanate compound (SN495V-CN) obtained in Synthesis Example 1, 16 parts by mass of 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane (BMI-80 (trade name), K.I Chemical Industry Co., LTD.), 16 parts by mass of a biphenyl aralkyl type maleimide compound (MIR-3000-MT (trade name), Nippon Kayaku Co., Ltd.), 20 parts by mass of a naphthol ether type epoxy resin (HP-6000 (trade name), epoxy equivalent: 250 g / eq., DIC Corporation), and the BaTiO2 obtained in Preparation Example 1 were mixed. 4 O 9 90 parts by mass (in terms of solid content) of the slurry (A) (solid content concentration 40%), 3 parts by mass of a silane coupling agent (KBM-403 (trade name), Shin-Etsu Chemical Co., Ltd.), 1 part by mass of DISPERBYK (registered trademark)-161 (trade name, BYK Chemie Japan KK) as a wetting and dispersing agent, and 2 parts by mass of DISPERBYK (registered trademark)-111 (trade name, BYK Chemie Japan KK) (total of wetting and dispersing agents: 3 parts by mass) were mixed to obtain a resin varnish (solid content concentration 50% by mass).

[0273] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0274] [Comparative Example 4]

[0275] A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 1 except that 10 parts by mass of fused spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica was 81:19 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0276] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0277] [Comparative Example 5]

[0278] A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 1 except that 280 parts by mass of molten spherical silica (SC4500-SQ (trade name)) was added instead of 19 parts by mass. 4 O 9 The mixing ratio (content ratio) of (A) and molten spherical silica is 14:86 by volume (BaTi 4 O 9 (A): fused spherical silica).

[0279] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0280] [Comparative Example 6]

[0281] Compounding barium titanate (BaTi 4 O 9 , average particle size (D50) 2.08 μm, BT-149 (trade name, Nippon Chemical Industry Co., Ltd.) 180 parts by mass in place of the BaTi obtained in Preparation Example 1 4 O 9 A resin varnish (solid content concentration 50% by mass) was obtained in the same manner as in Example 4 except that 90 parts by mass of the slurry of (A) was added. The mixing ratio (content ratio) of barium titanate and fused spherical silica in the resin varnish was 52:48 (barium titanate: fused spherical silica) by volume ratio.

[0282] Using the obtained resin varnish, a metal foil-clad laminate (double-sided copper-clad laminate) was produced in the same manner as in Example 1. The physical properties of the obtained resin varnish and metal foil-clad laminate were measured by the evaluation methods described below. Table 2 shows the measurement results.

[0283] [Evaluation Method]

[0284] (1) Evaluation of resin varnish (determination of resin curing time)

[0285] The resin varnishes obtained in Examples and Comparative Examples were injected into a measuring machine (automatic curing time measuring device MADOKA (trade name), Matsuo Sangyo Co., Ltd.) using a micropipette, and the time (seconds) until the resin was cured was measured under the following measurement conditions.

[0286] (Measurement conditions)

[0287] Hot plate temperature: 170° C., torque judgment value: 15%, rotation speed: 190 rpm, revolution speed: 60 rpm, gap value: 0.3 mm, averaging point number: 50, injection volume: 500 μL.

[0288] (2) Evaluation of Metal Foil-Clad Laminated Sheets

[0289] (Appearance evaluation)

[0290] The copper foil on both sides of the metal foil-clad laminate obtained in the examples and comparative examples was completely etched to obtain an unclad plate in which the copper foil on both sides was completely removed. Both sides of the unclad plate were visually observed, and the case where no unevenness occurred on both sides was evaluated as "A", and the case where unevenness occurred on at least one of the two sides was evaluated as "C".

[0291] (Glass transition temperature (Tg))

[0292] The copper foils on both sides of the metal foil-clad laminate obtained in the examples and comparative examples were completely etched to obtain an unclad plate in which the copper foils on both sides were completely removed. The unclad plate was cut (reduced) to a size of 40 mm × 4.5 mm to obtain a sample for measurement. The sample for measurement was used to measure the glass transition temperature (Tg, ° C) using a dynamic viscoelasticity analyzer (Q800 (trade name), TA Instrument) according to JIS C6481 by the DMA method.

[0293] (Coefficient of Thermal Expansion (CTE))

[0294] The copper foils on both sides of the metal foil-clad laminates obtained in the examples and comparative examples were completely etched to obtain unclad plates with all the copper foils on both sides removed. The unclad plates were cut (reduced) to a size of 40 mm × 4.5 mm to obtain a sample for measurement. The sample for measurement was used to measure the coefficient of thermal expansion (CTE, ppm / °C) at 60°C to 120°C using a thermomechanical analyzer (Q400 (trade name), TA Instrument) in accordance with JIS C6481, with the temperature increased from 40°C to 340°C at 10°C per minute.

[0295] (Relative dielectric constant (Dk) and dielectric loss tangent (Df))

[0296] The copper foil on both sides of the metal foil-clad laminate obtained in the examples and comparative examples is completely etched to obtain an unclad plate with the copper foil on both sides completely removed. The unclad plate is cut (reduced) to a size of 100 mm × 100 mm to obtain a sample for measurement. Using the sample for measurement, an open resonator (Fabry-Perot resonator DPS03 (trade name), KEYCOM Corp.) is used to measure the relative dielectric constant (Dk) and dielectric loss tangent (Df) at 40 GHz. It should be noted that the measurement of the relative dielectric constant (Dk) and dielectric loss tangent (Df) is carried out in an environment of temperature 23°C ± 1°C and humidity 50% RH ± 5% RH.

[0297] [Table 1]

[0298]

[0299] [Table 2]

[0300]

[0301] This application claims priority based on Japanese Patent Application No. 2021-020067 filed with the Japan Patent Office on February 10, 2021, the contents of which are incorporated herein by reference.

[0302] Industrial Applicability

[0303] The resin composition of the present invention has a high dielectric constant and a low dielectric loss tangent, as well as a low thermal expansion coefficient and a good appearance. Therefore, the resin composition of the present invention can be suitable as a raw material for, for example, a cured product, a prepreg, a film-like bottom filling material, a resin sheet, a laminate, a build-up material, a non-conductive film, a metal foil-clad laminate, a printed circuit board, a fiber-reinforced composite material, or used in the manufacture of a semiconductor device.

Claims

1. A resin composition comprising: BaTi4O9(A), A filling material (B) different from the BaTi4O9 (A), Thermosetting resin (C), Silane coupling agent, and Wetting and dispersing agents, The average particle size (D50) of the BaTi4O9 (A) is 0.10 to 1.00 μm. The average particle size (D50) of the filler (B) is 0.10 to 10.00 μm, The volume ratio of BaTi4O9 (A): the filler (B) is expressed as 15:85 to 80:20, including the BaTi4O9 (A) and the filler (B). The content of the silane coupling agent is 0.1 to 5.0 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition. The content of the wetting and dispersing agent is 0.5 to 5.0 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition. The content of BaTi4O9 (A) is 70 to 280 parts by mass relative to 100 parts by mass of the resin solid content in the resin composition. The content of the filler (B) is 10 to 220 parts by mass based on 100 parts by mass of the resin solid content in the resin composition. The content of the thermosetting resin (C) is 30 to 95 parts by mass relative to 100 parts by mass of the total of the BaTi4O9 (A) and the filler (B). The filler material (B) contains silicon dioxide.

2. The resin composition according to claim 1, wherein The total content of the BaTi4O9 (A) and the filler (B) is 100 to 300 parts by mass based on 100 parts by mass of the resin solid content in the resin composition.

3. The resin composition according to claim 1 or 2, wherein The thermosetting resin (C) includes one or more selected from the group consisting of cyanate compounds, maleimide compounds, epoxy compounds, phenol compounds, alkenyl-substituted nadic imide compounds, oxetane resins, benzoxazine compounds, and compounds having a polymerizable unsaturated group.

4. The resin composition according to claim 3, wherein The cyanate compound comprises one or more selected from the group consisting of phenol novolac type cyanate compound, naphthol aralkyl type cyanate compound, naphthyl ether type cyanate compound, xylene resin type cyanate compound, bisphenol M type cyanate compound, bisphenol A type cyanate compound, diallyl bisphenol A type cyanate compound, bisphenol E type cyanate compound, bisphenol F type cyanate compound, and biphenyl aralkyl type cyanate compound, and prepolymers or polymers of these cyanate compounds.

5. The resin composition according to claim 3, wherein The maleimide compound comprises one or more selected from the group consisting of bis(4-maleimidephenyl)methane, 2,2-bis(4-(4-maleimidephenoxy)-phenyl)propane, bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, a maleimide compound represented by the following formula (2), a maleimide compound represented by the following formula (3), and a maleimide compound represented by the following formula (4), In formula (2), R 1 Each independently represents a hydrogen atom or a methyl group, n1 is an integer of 1 to 10, In formula (3), R 2 Each independently represents a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, or a phenyl group, and n2 is an average value, which represents 1 <n2≤5, In the formula (4), Ra each independently represents a hydrogen atom, an alkyl, alkoxy or alkylthio group having 1 to 10 carbon atoms, an aryl, aryloxy or arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a nitro group, a hydroxyl group or a mercapto group, q represents an integer of 0 to 4, and when q is an integer of 2 to 4, Ra may be the same or different in the same ring, Rb each independently represents a hydrogen atom, an alkyl, alkoxy or alkylthio group having 1 to 10 carbon atoms, an aryl, aryloxy or arylthio group having 6 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, a halogen atom, a hydroxyl group or a mercapto group, r represents an integer of 0 to 3, and when r is 2 or 3, Rb may be the same or different in the same ring, and n represents the average number of repeating units, and represents a value of 0.95 to 10.

0.

6. The resin composition according to claim 3, wherein The epoxy compound includes one or more selected from the group consisting of biphenyl aralkyl epoxy resins, naphthalene epoxy resins, naphthyl ether epoxy resins, and butadiene skeleton-containing epoxy resins.

7. The resin composition according to claim 1 or 2, which is used for a printed circuit board.

8. A prepreg comprising: substrate; and, The resin composition according to any one of claims 1 to 7 impregnated or coated on the substrate. 9 . A resin sheet comprising the resin composition according to claim 1 . 10 . A laminate comprising one or more selected from the group consisting of the prepreg according to claim 8 and the resin sheet according to claim 9 .

11. A metal foil-clad laminate comprising: The laminated plate of claim 10; and A metal foil is disposed on one or both sides of the laminate.

12. A printed circuit board, comprising: Insulation layer; and, A conductor layer disposed on one or both sides of the insulating layer, The insulating layer comprises a cured product of the resin composition according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Film for packaging bag

    JP1991000301B2

  • Milliwave system

    JP2000091717A

  • Resin composition for printed wiring board, prepreg, resin sheet, laminate board, metal foil-clad laminate board, and printed wiring board

    JP2017195334A

  • Spacer for laminoplasty

    JP2021020067A

  • Maleimide, curable resin composition, and cured product

    WO2020217679A1